The steady-state economy - Daly, Herman (Henry Stewart Talks, 2023)
Economic growth, Growth metrics, Steady-state economy, Uneconomic growth, Migratory pressures, Population growth, Caring capacity, Applied hope, Resource-consumption constraints, Ecological economics, Entropy